A Cytometrist's Guide to Coordinating and Performing Effective COVID‐19 Research. Issue 1 (8th September 2020) - Chattopadhyay, Pratip K.; Filby, Andrew; Jellison, Evan R.; Ferrari, Guido; Green, Cherie; Cherian, Sindhu; Irish, Jonathan; Litwin, Virginia; ,
Abstract: Cytometry is playing a crucial role in addressing the COVID‐19 pandemic. In this commentary—written by a variety of stakeholders in the cytometry, immunology, and infectious disease communities—we review cytometry's role in the COVID‐19 response and discuss workflow issues critical to planning and executing effective research in this emerging field. We discuss sample procurement and processing, biosafety, technology options, data sharing, and the translation of research findings into clinical environments. © 2020 International Society for Advancement of Cytometry